Review: Challenges and opportunities of implementing mass productivity scale (MPS) at date farms in Malaysia - Asmaddy Haris; Aimi Fadzirul Kamarubahrin; Siti Nurazira Mohd Daud; Zurina Kefeli @ Zulkefli; Nursilah Ahmad; Nurul Aini Muhamed; Syadiyah Abdul Shukor (Jurnal Ilmu Pertanian, 2020)
The study aimed to review the challenges and opportunities of mass productivity scale (MPS) for the dates (Phoenix dactylifera L.) farm in Malaysia. The review on site and document was done to drill the issues faced by dates palm farmers. The common issues affecting dates farm in Malaysia were pest attack, import permit, lack of expertise, and climate and soil requirements. In a united response, the government should form the National Dates Palm Centre (NDPC) which will explore opportunities to address issues faced by the dates palm sector in Malaysia.